Heat transfer and entropy investigation of non-Newtonian nanofluid mixed convection in a cubic cavity with a wavy bottom wall under the influence of a magnetic field - Obai Younis; Aissa Abderrahmane; Ali B.M. Ali; Ahmed Rashad; Sameh E. Ahmed; Abed Mourad; Soheil Salahshour; Maboud Hekmatifar; Kamel Guedri (Case Studies in Thermal Engineering)
1)Background: This article reports 3D simulations of nanofluid motion within a three-dimensional cubic cavity occupied with a permeable medium. It was supposed that the motion region holds a hot spinning cylinder and has a wavy bottom plane with various undulation values. Also, the domain was separated into two levels., namely, the permeable layer and the power-law nanofluid layer. 2)Methods: The worked mixture is a non-Newtonian liquid, and the magnetic impacts are analyzed. The (FEM) with a triangle-shaped part form was used to resolve the governing formulas. The results were demonstrated for a variety of motion factors, including the cylinder's angular velocity (Ω = 0 to 2000), Hartmann number (Ha= 0-10), power-law index (n= 0.8, 1 and 1.4), and undulation numbers (N= 1 to 4). The effects of the different factors on motion, heat transmission, and entropy formation are illustrated in stream function, isotherms, and isentropic contours. Increased amounts of Ω, Da, N, φ, besides decreased values of Ha, enhance the heat transmission. 3)Significant Findings: The majority of entropy production is caused by heat transmission.; though liquid resistance and magneto impact also influence it.